2012
DOI: 10.1007/978-3-642-24986-0_2
|View full text |Cite
|
Sign up to set email alerts
|

VCSEL Fundamentals

Abstract: In this chapter we outline major principles of vertical-cavity surfaceemitting laser (VCSEL) design and operation. Basic device properties and generally applicable cavity design rules are introduced. Characteristic parameters like threshold gain and current, differential quantum efficiency and power conversion efficiency, as well as thermal resistance are discussed. We describe the design of Bragg reflectors and explain the transfer matrix method as a convenient tool to compute VCSEL resonator properties in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 148 publications
0
43
0
Order By: Relevance
“…The resulting thermal resistance (R thermal = ΔT/ΔP diss ) of our 980 nm VCSEL is ~2.8 K/mW. This value is about what would be expected (possibly slightly higher) for an oxide VCSEL with an oxide aperture diameter of ~7.0 μm [8]. We note that we may reduce the thermal resistance by replacing some or all of our high index AlGaAs DBR layers with GaAs high index DBR layers.…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…The resulting thermal resistance (R thermal = ΔT/ΔP diss ) of our 980 nm VCSEL is ~2.8 K/mW. This value is about what would be expected (possibly slightly higher) for an oxide VCSEL with an oxide aperture diameter of ~7.0 μm [8]. We note that we may reduce the thermal resistance by replacing some or all of our high index AlGaAs DBR layers with GaAs high index DBR layers.…”
Section: Resultsmentioning
confidence: 84%
“…GaAs-based infrared VCSEL with DBRs composed of AlGaAs [8]. The resulting thermal resistance (R thermal = ΔT/ΔP diss ) of our 980 nm VCSEL is ~2.8 K/mW.…”
Section: Resultsmentioning
confidence: 99%
“…Minimum threshold current (1.1 mA) is obtained for HC-VCSEL B which has the smallest gain-to-resonance detuning at 25°C. At higher ambient temperatures, HC-VCSELs C and D have lower threshold currents since the detuning is reduced with temperature as a result of the ∼4 times faster redshift of the gain peak with respect to the cavity resonance [15]. The threshold currents from Fig.…”
Section: A Static Performancementioning
confidence: 90%
“…Despite the development in the technology, the existing models for the modulation performance of VCSELs and semiconductor lasers in general are still ineffective. The existing models of modulation response are based on many parameters whose values can be chosen arbitrarily to a certain extent, or have to be fitted to experiment [10][11][12][13][14][15][16]. These models have shown that the approach based on rate equations can give good agreement with the small-signal modulation (SSM) response experiment.…”
Section: Introductionmentioning
confidence: 99%